Atividade da fração proteolítica P1G10, derivada do latex de V.Cundinamarcensis, contra danos celulares e moleculares induzidos pela exposição aguda à radiação Ultravioleta B. - Kátia Michelle Freitas (2016)
P1G10 is a fraction rich in cysteine proteases, obtained from Vasconcellea cundinamarcensis latex, by chromatographic separation (Sephadex G10). Previous studies have demonstrated antitumor activity against murine melanoma, healing action in different models of skin lesions, and protective/healing effect against gastric ulcers, where it was suggested a possible antioxidant activity. In this study, we evaluated the effect of topical treatment with P1G10 on factors involved in cellular and molecular damage induced by UVB radiation, using in vivo and in vitro models. In lesions induced by single exposure to UVB, P1G10 reduced edema and erythema, increased hypodermis cellularity, MPO activity (33%), TNF-α (32%) and IL1β (31%) levels and CO2 expression. These results indicate a significant anti-inflammatory effect and seem to be related to the reduction of Akt expression promoted by treatment with P1G10. This fraction also showed antioxidant activity: P1G10 treatment inhibited the depletion of GSH, GPx, SOD caused by UVB radiation and increased the activity of catalase (50%). This possibly contributed to the significant reduction on MDA levels (52%), observed in groups treated with P1G10. Combined with anti-inflammatory and antioxidant effects, our results inferred that topical treatment with P1G10 protect skin cells from extracellular matrix and DNA damage induced by radiation: in the groups treated with the fraction, MMP-9 activity and caspase 3 expression were reduced and an increase in p53 expression was detected. Another indication of this antioxidant and protective of P1G10 was demonstrated by in vitro analysis. The treatment of keratinocytes (HaCat cells) promoted an increase in cell viability and significantly reduced ROS production in cells irradiated by UVB. P1G10 also displays an intrinsic antioxidant activity as proven by radical derating DPPH• property (EC50 = 20.35 ± 0.66 mg / mL). In skin lesions promoted by repeated exposure to UVB, topical application of P1G10 reduced ROS formation (47%), however, did not alter the MDA levels or SOD activity. The fraction also preserved the levels of GSH and GPx and increased catalase levels, protecting the skin antioxidant system. In this model we also observed an antiinflammatory effect of P1G10 through reduction of TNF-α levels (73%) and IL1β (92%) levels, and decrease of cellularity and inflammatory infiltrate in hypodermis. UVB-induced epidermal hyperplasia was inhibited by the P1G10 which was evidenced by a decrease in epidermal thickness and in immunostaining for PCNA in keratinocytes. These events may be related to the anti-inflammatory effect P1G10 combined with antioxidant activity, which was associated with reduced MMP-9 activity and minor phosphorylation of the proteins of MAP kinases (JNK and p-38) and Akt, as observed in treated animals. Given the above, it is suggested that P1G10 has interesting antioxidant and anti-inflammatory actions that may contribute to tissue repair of damage caused by exposure to UVB.